ANALISIS PERBEDAAN PEMAHAMAN MAHASISWA PENDIDIKAN EKONOMI ANTARA LULUSAN IPS DAN NON-IPS TERHADAP KONSEP DASAR AKUNTANSI DI UNIVERSITAS RIAU - Shella Junira Junira; Gusnardi '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: One of the keys to mastering the science of accounting is to understand the basic concepts of accounting. Where the basic concepts of accounting includes the assets, liabilities (debts) and capital. This study aims to measure the level of understanding of the basic concepts of accounting views of accounting students who come from backgrounds different secondary education is high school social studies courses and high school science courses and also aims to determine the differences in the perception of the student or the student's understanding of the basic concepts of accounting. The method used is a method of quantitative desriptif. The population in this study were all students of class of 2012 and 2013 Economic Education Studies Program, University of Riau whohave completed the course Fundamentals of Accounting I and Accounting Basics II, consist of four classes with 152 students and the number of establishment of the samples using the technique Simple Random sampling totaling 63 people. Then determined the amount of each sample according to the school of originis Disproportionate Stratified Random Sampling. The data used is primary data that questionnaires (questionnaire) filled respondents and secondary data obtained through literature studies conducted on the books and records obtained under the related research. From the results of this study concluded that: (1) Of the three variables were used as the measurement differences in the level of students 'understanding of the basic concepts of accounting are assets, liabilities, and capital otherwise there are differences in students' understanding of the basic concepts of accounting significantly. (2) From the Department of Social and senior high school science courses have a p-value <0.05, meaning that there is a difference between the variables of the basic concepts of accounting for student understanding. Keywords : basic conceptsof accounting, studentcomprehension